The Impact of Sibling Age Gap, Stimulation, Father Involvement, and Parenting Stress on the Development of Children Aged 36-59 Months: A Multilevel Analysis - Rachmawati, Rulita Ayu; Adriani, Rita Benya; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Early childhood development (36-59 months) is a critical period that significantly influences a child's growth, learning and overall well-being. Providing high-quality early childhood care and education is essential to maximizing children's potential for later success, as it equips them with the skills and competencies necessary for their future development. Subjects and Method: This study used a cross-sectional approach conducted in 28 Early Childhood Education (PAUD) in Wonogiri Regency, Central Java in August - September 2024. A total of 225 children aged 36-59 months were selected in this study with a randomized controlled trial (RCT). The dependent variable of this study was the development of children aged 36-59 months. The independent variables at level 1 were the age gap between children, parenting stimulation, father involvement and parenting stress. The independent variable at level 2 was Early Childhood Education (PAUD). Data were collected through questionnaires and the analysis of this study used multilevel multiple logistic regression and used STATA 13. Results: This multilevel multiple logistic regression analysis concluded that age-appropriate child development at 36–59 months increased with longer age gaps between children (OR=2.06; CI 95%= 0.97 to 4.42; p = 0.061), high parenting stimulation (OR=2.04; CI 95%= 1.30 to 3.20; p = 0.002), father's involvement (OR=2.74; CI 95%= 1.22 to 6.15; p= 0.014). Child development appropriate for the age of 36-59 months old decreased with high parenting stress (OR=0.34; 95% CI= 0.20 to 0.57; p < 0.001). Early Childhood Education (PAUD) was not statistically significant in influencing early childhood development with ICC = 0.36%< 8-10%. Conclusion: The development of children aged 36-59 months increased significantly with the age gap of children, nurturing stimulation, and father involvement in nurturing. Child development decreased with high parenting stress. Early Childhood Education (PAUD) has a low contextual effect on the development of children aged 36-59 months.